The differential mobilization of human neutrophil granules. Effects of phorbol myristate acetate and ionophore A23187. - Wright, D. G. (1977)
Phorbol myristate acetate (PMA, 2 to 100 ng/ml) and ionophore A23187 (10(-7) to 10(-6) M) cause human neutrophils to release up to 50% of the granule-associated enzyme lysozyme extracellularly without release of beta-glucuronidase or the cytoplasmic enzyme LDH. When azurophil and specific granules are separated from neutrophil lysates by sucrose density centrifugation, it is found that lysozyme release from neutrophils exposed to PMA or to A23187 reflects a selective disappearance of the small, peroxidase-negative (specific) granules from the cells. These studies demonstrate that neutrophils can mobilize the specific and azurophil granules independently. These studies also demonstrate that under certain conditions the specific granules of human neutrophils behave like the storage granules of secretory cells. Finally, these studies show that techniques of separating neutrophil granules according to their sedimentation characteristics successfully divide these granules into populations that are distinct not only by cytochemical and morphologic criteria but also according to their availability for mobilization and extracellular release. (APM J Pathol 87:273-284, 1977).